Pengaruh Venting dan Temperatur pada Kegiatan Bongkar Muat LPG di Kapal Fully Refrigerated LPG/C Prima Lautan II - Ardani, Indah Rika; Wahyuni, Eni Tri; Indriyati, Retno (Politeknik Bumi Akpelni Semarang, 2026)
Venting and temperature are important factors that can affect the efficiency and safety of the LPG loading and unloading process, especially on ships with a fully refrigerated system. This research aims to determine the effect of venting and temperature on LPG loading and unloading activities on the fully refrigerated LPG/C Prima Lautan II ship. This research uses a quantitative approach with survey methods. Data analysis was carried out using multiple linear regression to determine the simultaneous and partial influence of the independent variables (venting and temperature) on the dependent variable (LPG loading and unloading efficiency). The analysis results show that both venting and temperature have a significant effect on loading and unloading activities. Venting contributes to keeping the pressure stable during the process, while temperature has an influence on the evaporation speed and LPG vapor pressure in the tank. The significance value for both variables is less than 0.05, indicating that statistically both have a real influence on the efficiency of LPG loading and unloading activities. The results of the research indicate that if the ventilation and handling work simultaneously well, smooth LPG loading and unloading activities will be achieved on the LPG/C Prima full refrigerated ship. Lautan II.